2018
DOI: 10.1002/ehf2.12294
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive cardiomyopathy: an unusual phenotype of a lamin A variant

Abstract: Most individuals with cardiomyopathy associated with variants of the LMNA (lamin A) gene present with cardiac conduction abnormalities followed by dilated cardiomyopathy and cardiac failure; some also have skeletal muscle weakness. In this report, an individual with restrictive cardiomyopathy presenting with conduction defects followed by cardiac dysfunction of a restrictive nature eventually requiring cardiac transplantation is described. Subsequently, progressive skeletal muscle weakness became evident. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…Recently, Paller et al found a 1 bp deletion in exon 5 of the LMNA gene (c.835delG, p.E279RfsX201) in a RCM patient who developed additionally skeletal muscle weakness and atrial fibrillation [41]. Histology analysis revealed hypertrophy and cardiac fibrosis in the explanted myocardial tissue [41].…”
Section: Lamin A/c (Lmna)mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Paller et al found a 1 bp deletion in exon 5 of the LMNA gene (c.835delG, p.E279RfsX201) in a RCM patient who developed additionally skeletal muscle weakness and atrial fibrillation [41]. Histology analysis revealed hypertrophy and cardiac fibrosis in the explanted myocardial tissue [41].…”
Section: Lamin A/c (Lmna)mentioning
confidence: 99%
“…Recently, Paller et al found a 1 bp deletion in exon 5 of the LMNA gene (c.835delG, p.E279RfsX201) in a RCM patient who developed additionally skeletal muscle weakness and atrial fibrillation [41]. Histology analysis revealed hypertrophy and cardiac fibrosis in the explanted myocardial tissue [41]. Beside RCM, LMNA mutations cause DCM [187], ACM [188], LVNC [189], Emery-Dreifuss muscular dystrophy (MIM, #181350) [190], familial lipodystrophy (MIM #151660) [191] and Hutchinson-Gilford progeria syndrome (HGPS, MIM #176670) [192].…”
Section: Lamin A/c (Lmna)mentioning
confidence: 99%
“…Thus, pacemakers are much more frequently implanted than implantable cardioverter-defibrillator (ICD) in desminopathic patients. Cardiomyopathy is usually dilated, but can be sometimes hypertrophic (HCM) or restrictive (RCM) in desminopathy [ 61 ], while these forms are very rare in cardiac laminopathies [ 46 , 54 , 62 ]. In addition, desmin mutations have recently been found in a subset of patients suffering from arrhythmogenic right ventricular cardiomyopathy (ARVC) [ 63 ].…”
Section: Desminopathiesmentioning
confidence: 99%
“…146 Mutations in all these genes are involved in DCM as well as in rare cases of ACM. [148][149][150][151] Other cytoskeletal proteins involved in DCM are desmin (DES), dystrophin (DMD), alpha-dystroglycan (DAG1), dystrobrevin (DTNA), sarcoglycan (SGCD), syntrophin (SNTA1), phospholamban (PLN), caveolin (CAV3).…”
Section: Dilated Cardiomyopathymentioning
confidence: 99%